Fetal acetylcholine receptor inactivation syndrome: A myopathy due to maternal antibodies. Issue 1 (February 2015) - Hacohen, Yael; Jacobson, Leslie W.; Byrne, Susan; Norwood, Fiona; Lall, Abhimanu; Robb, Stephanie; Dilena, Robertino; Fumagalli, Monica; Born, Alfred Peter; Clarke, Debbie; Lim, Ming; Vincent, Angela; et al.
Abstract : Background: Transient neonatal myasthenia gravis (TNMG) affects a proportion of infants born to mothers with myasthenia gravis (MG). Symptoms usually resolve completely within the first few months of life, but persistent myopathic features have been reported in a few isolated cases. Methods: Here we report 8 patients from 4 families born to mothers with clinically manifest MG or mothers who were asymptomatic but had elevated acetylcholine receptor (AChR) antibody levels. Results: Clinical features in affected infants ranged from a mild predominantly facial and bulbar myopathy to arthrogryposis multiplex congenita. Additional clinical findings included hearing impairment, pyloric stenosis, and mild CNS involvement. In all cases, antibodies against the AChR were markedly elevated, although not always specific for the fetal AChR γ subunit. There was a correlation between maternal symptoms; the timing, intensity, and frequency of maternal treatment; and neonatal outcome. Conclusions: These findings suggest that persistent myopathic features following TNMG may be more common than currently recognized. Fetal AChR inactivation syndrome should be considered in the differential diagnosis of infants presenting with unexplained myopathic features, in particular marked dysarthria and velopharyngeal incompetence. Correct diagnosis requires a high degree of suspicion if the mother is asymptomatic but is crucial considering the high recurrence risk for future pregnancies and the potentially treatable nature of this condition. Infants with a history of TNMG should be followed up for subtle myopathic signs and associated complications.